Online Routine Activities and Self-Guardianship against Cyber Abuse. Issue 4 (19th May 2023) - Vakhitova, Zarina I.; Alston-Knox, Clair L.; Mawby, Rob I.
ABSTRACT: This study examines the effect of online lifestyles and routine activities on self-guardianship against cyber abuse. The data from a sample of U.S. adults ( N = 746) was modeled using a binary logistic regression and Bayesian variable selection with the stochastic search algorithm. We found that, on average, victims who employ self-guardianship tend to be less engaged in online routine activities than victims who do not, suggesting online routine activities are not only an important risk factor for victimization in line with previous research, but they also affect victims' decision-making about self-guardianship.